Gresham's Law and the Demand for NRU's and SDR's: A Reply - Aliber, Robert Z. (Quarterly Journal of Economics, 1969)
Journal Article Gresham's Law and the Demand for NRU's and SDR'S: A Reply Get access Robert Z. Aliber Robert Z. Aliber University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 83, Issue 4, November 1969, Pages 704–705, https://doi.org/10.2307/1885459 Published: 01 November 1969